Синтез швидкодіючих багатозначних структур мовних систем штучного інтелекту - Бондаренко, М. Ф.; Ревенчук, І. А.; Четвериков, Г. Г. (My University, 1998)
Синтез швидкодіючих багатозначних структур мовних систем штучного інтелекту